Brokers and Saboteurs: Actor Roles in Destination Innovation Network Development. Issue 5 (3rd September 2021) - Sørensen, Flemming; Balsby, Nanna
ABSTRACT: In many tourist destinations, innovation network development is complicated because relevant actors have divergent interests with respect to destination development. This article reports a longitudinal case study of a destination innovation network within a small tourist destination. The network in question formed in spite of fierce conflict between destination actors. The article illustrates how different network actor roles make innovation network development possible, and how other roles make it troublesome. The findings emphasise how the right mix, timing, and interplay of various actor roles is crucial for innovation network building in conflict-dominated tourist destinations.